Evaluation of a pharmacist-led outpatient direct oral anticoagulant service. - Ashjian, Emily; Kurtz, Brian; Renner, Elizabeth; Yeshe, Robert; Barnes, Geoffrey D. (American Journal of Health-System Pharmacy, 2017)
Purpose. The impact of a pharmacist-led direct oral anticoagulant (DOAC) service on prescription appropriateness and patient adherence was simultaneously evaluated. Methods. In this retrospective analysis, patients age 18 years or older for whom a DOAC was prescribed from September 20, 2013, through December 31, 2014, were identified through electronic medical record review of all DOAC prescriptions within the University of Michigan Health System. Patients had their DOAC therapy managed by a pharmacist-led DOAC service or by their physician (usual care). Primary endpoints included the percentage of patients who had appropriate DOAC therapy prescribed at baseline and at follow-up appointments at 3-6 months. Secondary endpoints included mean medication possession ratios (MPRs). Results. A total of 258 patients were included in the study, with 129 in each group. Patients in the pharmacist-led DOAC service were significantly more likely to have an appropriate combination of DOAC and dosage prescribed for their indication at baseline compared with the usual care group (p = 0.009), a finding that persisted at follow up (p = 0.016). There was no significant difference between groups in the number of patients determined to have an appropriate DOAC prescribed for an approved indication (independent of dose) in the pharmacist-led service (95.3%) versus usual care (93.0%) at baseline. Patients in the pharmacist-led service had a greater mean adjusted MPR compared with the usual care group (p = 0. 0014) over a median follow-up period of 248 days. Conclusion. A pharmacist-led DOAC service increased appropriate dosing of DOACs at baseline and follow up as well as patient adherence to therapy.